2020
DOI: 10.1186/s12906-020-03023-1
|View full text |Cite
|
Sign up to set email alerts
|

The botanical origin and antioxidant, anti-BACE1 and antiproliferative properties of bee pollen from different regions of South Korea

Abstract: Background Bee pollen (BP) has been used as a traditional medicine and food diet additive due to its nutritional and biological properties. The potential biological properties of bee pollen vary greatly with the botanical and geographical origin of the pollen grains. This study was conducted to characterize the botanical origin and assess the antioxidant effects of ethanol extracts of 18 different bee pollen (EBP) samples from 16 locations in South Korea and their inhibitory activities on human β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
(70 reference statements)
0
13
0
Order By: Relevance
“…The use of natural products such as beehive products including honey, pollen, royal jelly, and propolis as a source of antioxidant molecules has been supported and suggested to protect human cells from the effects of oxidative stress by numerous scientific studies [ 142 ]. Moreover, the antioxidant activities of bee pollen have been evaluated in several works using well-known techniques such as DPPH, ABTS, β- carotene, FRAP, CUPRAC, NO, and TAC assays [ 132 , 138 , 140 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Table 3 summarizes all studies that have evaluated the antioxidant activity of bee pollen.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of natural products such as beehive products including honey, pollen, royal jelly, and propolis as a source of antioxidant molecules has been supported and suggested to protect human cells from the effects of oxidative stress by numerous scientific studies [ 142 ]. Moreover, the antioxidant activities of bee pollen have been evaluated in several works using well-known techniques such as DPPH, ABTS, β- carotene, FRAP, CUPRAC, NO, and TAC assays [ 132 , 138 , 140 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Table 3 summarizes all studies that have evaluated the antioxidant activity of bee pollen.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Other research works reported a variable antioxidant effect of different bee pollen extracts including those from Algeria, Greece, Italy, Korea, Spain, Slovakia, Malaysia, Serbia, Thailand, and Poland, and this variability can be significantly related to a variety of botanical and geographical origins [ 132 , 140 , 143 , 147 , 148 , 153 , 154 , 156 , 158 , 159 , 163 , 164 , 165 , 170 ].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…However, it inhibits intracellular tyrosinase (TYR) and interfere with the expression of mRNA corresponding to TYR and tyrosinase receptor, TRP-1 and TRP-2 [119]. Bee pollens collected from different places in South Korea were tested against human prostate adenocarcinoma (PC-3), human lung carcinoma (NCI-H727), human lung carcinoma (A549), MCF-7, and AGS, resulting in IC 50 values between 0.9 to >25 mg/mL [120]. Stronger anticancer properties were shown by enzymatically cleaved bee pollen proteins, also known as the hydrolysates.…”
Section: Anticancer Properties Of Bee Productsmentioning
confidence: 99%
“…BP antioxidant activity is one of its most studied properties [ 99 ]. This bioeffect, which usually results from a combination of diverse mechanisms [ 79 ], is almost universally present in BP as it was always reported by published studies that searched for it, disregarding when and where they were undertaken [ 9 , 32 , 60 , 74 , 79 , 100 , 101 , 102 , 103 , 104 , 105 ]. Moreover, it has marked significance for its anti-inflammatory potential [ 65 , 101 ].…”
Section: Resultsmentioning
confidence: 99%